Observations on the time budget and diving ecology of Long-tailed Ducks in Eqalungmiut Nunaat, West Greenland - Reynolds, Peter (Wildfowl, 1987)
Aspects of the time budget and diving ecology of Long-tailed Ducks Clangula hymalis were studied in July 1984 at five plateau lakes in West Greenland. Examination of diurnal behaviour showed that peak vigilance levels may be correlated with peak Arctic Fox Alopex lagopus activity, although the two variables may be independently related to other factors. Males spent significantly more time alert and less time resting than females. For both sexes dive times and dive intervals varied significantly between sites. Male dive times were longer than those of females, probably as a consequence of physiological differences in diving capacity associated with body size, but dive intervals were not significantly different. Dive times and dive intervals were positively correlated. Females appeared to compensate for shorter dive times by increasing dive frequency and one female exploited the resources of the lake systematically, probably in response to local resource depletion and disturbance.